La formación de los jóvenes en liderazgo ambiental como un factor de apropiación territorial: el caso de la IED Eduardo Umaña Mendoza. (2017)
This paper analyzes the way the way in which leadership training processes are structured in school environmental education, and how these skills can become determinants in the perception and territorial appropriation of young people, based on the study case of school district Eduardo Umaña Mendoza in Bogotá. The paper reviews the legal provisions on school environmental education in Colombia, analyzes the dynamics of environmental education developed in said institution, and reflects on the process of territorial appropriation of young environmental leaders.Four teachers and eighty students from the selected school took part in the investigation; together with three young community leaders who joined the school project. The methodological design included interviews, surveys, and document review. The analysis of the instruments revealed relationships between the processes of leadership training from the school and the ways in which young people perceive their territory and act in the face of environmental problems. Thus, the territorial environment defines the environmental leader, and the school must be more involved in their training process, contemplating factors such as culture, territorial identity, and providing students with contextual knowledge, as well as encouraging their sense of belonging.